The next millennium and epidemiology: searching for information - Castiel Luis David (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
On the eve of the new millennium, it has become 'natural' to admit the emergence of tendencies to perform evaluations and inventories of the past and attempts to forecast future scenarios. While recognizing the ensuing uncertainties, the current paper takes this point of view as the point of departure for proposing a discussion on the future directions and prospects of epidemiology. Based on the pertinent analyses performed by the Sussers (father and son), I approach and discuss the scope and limits of new aspects assumed by the field, especially to the extent that it has included techniques and instruments from bioinformatics and molecular biology. In the latter areas (amongst many others), the notion of information has gained enormous importance. I then proceed to analyze the conceptual origins and shifts in this notion, in addition to possible repercussions and effects on the field of biological sciences in general and their research practices in particular.